Pluralisme Hukum dan Negosiasi Identitas: Analisis Komparatif Pasuwitan Masyarakat Adat Samin dalam Perspektif Hukum Keluarga Indonesia - Muhammad Nabil; Muhammad Ismail (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2026)
This study examines the socio-juridical tension surrounding Pasuwitan the unregistered marriage practice of the Samin Indigenous People (Sedulur Sikep) who ideologically reject state formalities. Within Indonesia's legal pluralism, this customary practice clashes with national family law, especially the Compilation of Islamic Law (KHI), which prioritizes formal registration. Using a qualitative socio-juridical approach grounded in Interpretive Anthropology, Legal Pluralism, and Legal Culture theories, and drawing on systematic library research of legislation, court decisions, and scholarly literature on family law and Samin customary marriage, the study finds that Pasuwitan embodies living law, upholding ethical norms like lifelong monogamy (siji kanggo selawase) while substituting formal Islamic marriage requirements (e.g., ijab qabul, wali) with verbal vows. Consequently, such unions are legally classified as nikah siri, rendering offspring "illegitimate" and obstructing access to civil rights and identity documentation. Although Constitutional Court Decision No. 97/PUU-XIV/2016 facilitates registration for Penghayat Kepercayaan (including Samin) at civil offices (Dukcapil), implementation triggers cultural ambivalence: elders resist formalization on principle, while youth pragmatically seek legal recognition. This intergenerational negotiation reflects living law adapting under state formalism. The Samin case thus illuminates asymmetric legal pluralism in Indonesian family law.